Perilaku Menyimpang Siswa dan Upaya Guru PPKn dalam Mengatasinya - Septiani, Depi; Ananda, Azwar; Montessori, Maria; Indrawadi, Junaidi (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This research endeavors to elucidate the root causes of deviant behavior exhibited by students enrolled at SMP Negeri 30 Padang. Employing a qualitative approach with a descriptive framework, data collection entailed purposive sampling through interviews, observations, and document analysis. The findings of this investigation reveal various manifestations of deviant behavior among students at SMP Negeri 30 Padang, encompassing the consumption of explicit content, smoking within the school premises, and engaging in bullying activities. The contributory factors identified include familial influences, peer associations, and community dynamics. In addressing students' deviant behavior, Pancasila and Citizenship Education teachers adopt a multifaceted approach. They employ preventative measures by actively supporting students in extracurricular activities within the school environment. Additionally, they employ repressive strategies, offering guidance and issuing warnings to students, and, finally, curative measures involving the provision of counseling services for necessary intervention and rehabilitation. This study provides valuable insights into the complexities of deviant behavior among students and offers potential avenues for its mitigation within the school context.